2010
DOI: 10.1139/z10-007
|View full text |Cite
|
Sign up to set email alerts
|

Influence of incubation temperature on morphology and locomotion performance of Leatherback (Dermochelys coriacea) hatchlings

Abstract: Abstract:The journey of Leatherback (Dermochelys coriacea (Vandelli, 1761)) hatchlings from nest to the sea is a vulnerable life-history stage. Studies have shown that nest incubation temperatures influence hatchling morphology and locomotor performance, which may affect hatchling fitness. We obtained incubation temperature profiles from 16 Leatherback nests in Tobago, West Indies, during the 2008 nesting season (March-June). There was significant variation among mean nest incubation temperatures, which had a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 28 publications
0
28
0
Order By: Relevance
“…Direct links between turtle hatchling morphology and fitness have been previously proposed (Ashmore and Janzen 2003;Booth 2006;Burgess et al 2006;Mickelson and Downie 2010;Micheli-Campbell et al 2012;Read et al 2013;Refsnider 2013), and any change in mass as a result of abiotic stress has the potential to affect hatchling survival during their initial journey from the nest to the sea, a stage in which they face a substantial predatory threat from canids, feral/domestic dogs, birds, and ghost crabs. A negative change in marine turtle hatchling mass has been shown to be accompanied by a decrease in flipper size and a decline in terrestrial locomotion performance (Mickelson and Downie 2010). Conversely, Refsnider (2013) showed that an increase in diel thermal variation increased hatchling speed in freshwater turtles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Direct links between turtle hatchling morphology and fitness have been previously proposed (Ashmore and Janzen 2003;Booth 2006;Burgess et al 2006;Mickelson and Downie 2010;Micheli-Campbell et al 2012;Read et al 2013;Refsnider 2013), and any change in mass as a result of abiotic stress has the potential to affect hatchling survival during their initial journey from the nest to the sea, a stage in which they face a substantial predatory threat from canids, feral/domestic dogs, birds, and ghost crabs. A negative change in marine turtle hatchling mass has been shown to be accompanied by a decrease in flipper size and a decline in terrestrial locomotion performance (Mickelson and Downie 2010). Conversely, Refsnider (2013) showed that an increase in diel thermal variation increased hatchling speed in freshwater turtles.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, although nesting earlier may avoid detrimental mean incubation temperatures, the effects of thermal variance, if independent of the high thermal limits experienced at Alagadi, may persist. Whether hatchlings will be faster, as suggested by Refsnider (2013), or suffer costs to terrestrial locomotion, as suggested by Mickelson and Downie (2010), it is evident that the mechanisms governing this relationship need to be explored in more depth and the fitness consequences and potential adaptive benefits of such a response should be investigated in more detail. This study highlights the need for further research into how different patterns of temperature variation affect reptilian offspring and the mechanisms driving these changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A negative correlation between incubation temperature and sea turtle hatchling size has been documented in all species of sea turtle studied (Hewavisenthi & Parmenter, 2001;Booth et al, 2004;Ischer et al, 2009;Mickelson & Downie, 2010;Booth & Evans, 2011;Maulany et al, 2012a;Read et al, 2012;Wood et al, 2014). Similarly, I found that hatchlings from nests with a T3dm above 34°C…”
Section: Hatchling Size and Massmentioning
confidence: 73%
“…Incubation temperatures that are too low or too high are lethal to the embryo (Hubert, 1985;Miller, 1985), however non-lethal incubation temperatures can also affect a range of hatchling attributes including sex (Valenzuela, 2004;Valenzuela & Lance, 2004), size (Ji et al, 2002;Booth et al, 2004), body shape (Mickelson & Downie, 2010), colouring (Deeming, 2004), metabolic rate (Steyermark & Spotila, 2000), growth rate O'Steen, 1998;Rhen & Lang, 1999;Booth et al, 2004), locomotor performance (Janzen, 1993b;Doody, 1999;Booth et al, 2004), thermoregulatory behaviour (Blumberg et al, 2002;Goodman & Walguarnery, 2007), incidence of deformities and fluctuating asymmetry (Elphick & Shine, 1998;Brana & Ji, 2000;Ji et al, 2002), survival (Billett et al, 1992) and behaviour (Burger, 1998). For these reasons nest temperature and possible changes to nest temperatures are predicted to have a major influence on life history characteristics and viability of oviparous reptile populations.…”
Section: General Introductionmentioning
confidence: 99%